Salvage External Beam Radiotherapy for Local Recurrence without Systemic Progression or Prostate Specific Antigen Recurrence of Prostate Cancer after Initial Hormonal Therapy: Is It Possible to Identify Patients Likely to Have Good Treatment Outcomes? - Kurokawa, Kohei; Ito, Kazuto; Suzuki, Kazuhiro; Ono, Yoshihiro; Yamamoto, Takumi; Akimoto, Tetsuo; Yamanaka, Hidetoshi (Japanese journal of clinical oncology, 2002)
Background: We attempted to identify factors that predict the outcomes of salvage external beam radiotherapy (sEBRT) in patients who showed local recurrence without systemic progression or isolated prostate specific antigen (PSA) recurrence after initial hormonal therapy. Methods: The subjects were 33 patients who were diagnosed as having local recurrence without systemic progression (30 cases) or isolated PSA recurrence (three cases). Of these patients, those with continuously decreasing PSA levels, which were 1.0 ng/ml or less 1–1.5 years after sEBRT, were regarded as good responders (GR) whereas the remaining patients were regarded as poor responders (nGR). Survival rates in these patients and factors that distinguish GR from nGR were evaluated retrospectively. Results: The cancer-specific 10-year survival rate was 82.4% in the 33 patients, 100% in the 21 GR patients and 55% in the 12 nGR patients (P < 0.0001). Stepwise variable selection to discriminate between GR and nGR revealed that the time from sEBRT initiation to the nadir PSA was the most significant factor (P = 0.000097). Before sEBRT, GR can be predicted in patients with pre-sEBRT PSA <30.0 ng/ml and PSA doubling time (PSADT) >7.0 months, with a sensitivity of 95.2% (20/21), a specificity of 100% and an accuracy of 97.0%. Conclusion: Good responses to sEBRT can be expected in patients with local recurrence without systemic progression or isolated PSA recurrence after initial hormonal therapy when the patients show both pre-sEBRT PSA <30.0 ng/ml and PSADT >7.0 months.